Non-Preferential Trading Clubs - Pascalis Raimondos-Møller; Alan D. Woodland (Copenhagen Business School (CBS), Department of Economics, 2006)
This paper examines the welfare implications of non-discriminatory tariff reforms by a subset of countries, which we term a non-preferential trading club. We show that there exist coordinated tariff reforms, accompanied by appropriate income transfers between the member countries, that unambiguously increase the welfare of these countries while leaving the welfare of non-members unaltered. In terms of economic policy implications, our results show that there exist regional, MFN-consistent arrangements that lead to Pareto improvements in world welfare.
hdl:10398/7540
Keywords: F15; 330; Trading clubs; non-preferential tariff reform; Kemp-Wan-Ohyama proposition